Consumers’ Attitudes toward the Use of an Edible Coating for Lamb Meat According to Label Information - Mauricio, Raquel Alves [UNESP]; Deliza, Rosires; Nassu, Renata Tieko (MDPI, 2022)
The use of edible coatings in meat is currently being investigated in several studies. However, consumers’ attitudes toward this technology are not clear. This study evaluated consumers’ intention to purchase vacuum-packaged meat with a chitosan coating based on the label information. Three factors combined with different levels were considered: type of cut (“loin”, “French rack”, or “leg steak”), coating/information (no information, chitosan without information explained, and chitosan with information explained), and price (low or high). Consumers’ purchase intentions were evaluated using a 7-point structured scale (1 = certainly would not buy; 7 = certainly would buy). The data were analyzed by conjoint analysis and cluster analysis. The average purchase intention value was 4.3 ± 0.5. The “French rack” cut showed the highest value for purchase intention and a high price was also a relevant factor. The packaging with the label stating the presence of a “chitosan” coating without giving any further information obtained higher purchase intentions than the one with the more detailed information label. In the cluster analysis, the factor “type of cut” showed the highest relative importance in two groups, while “price” had a higher impact in another. The type of cut was the main factor affecting consumers’ purchase intentions. However, different attitudes were observed depending on the group.
Keywords: Chitosan; Conjoint analysis; Packaging; Purchase intention